Leaf herbivory imposes fitness costs mediated by hummingbird and insect pollinators - Chautá, Alexander (PLoS One, 2017)
Plant responses induced by herbivore damage can provide fitness benefits, but can also have important costs due to altered interactions with mutualist pollinators. We examined the effects of plant responses to herbivory in a hummingbird-pollinated distylous shrub, Palicourea angustifolia. Through a series of field experiments we investigated whether damage from foliar herbivores leads to a reduction in fruit set, influences floral visitation, or alters floral traits that may influence pollinator preference or pollinator efficiency. Foliar herbivory by a generalist grasshopper led to reduced fruit set in branches that were directly damaged as well as in adjacent undamaged branches on the same plant. Furthermore, herbivory resulted in reduced floral visitation from two common hummingbird species and two bee species. An investigation into the potential mechanisms behind reduced floral visitation in induced plants showed that foliar herbivore damage resulted in shorter styles and lower nectar volumes. This reduction in style length could reduce pollen deposition between different floral morphs that is required for optimal pollination in a distylous plant. We did not detect any differences in the volatile blends released by damaged and undamaged branches, suggesting that foliar herbivore-induced changes in floral morphology and rewards, and not volatile blends, are the primary mechanism mediating changes in visitation. Our results provide novel mechanisms for how plant responses induced by foliar herbivores can lead to ecological costs.